Makerspace for Innovation Learning: How Finnish Comprehensive Schools Create Space for Makers - Juha Jaatinen; Eila Lindfors (The Design and Technology Association, 2022)
Finland has its very own version of a “makerspace”: crafts class. Originally one for boys and one for girls. Later for different materials, especially for wood and textile, that are deep-rooted concepts in Finnish mindset about crafts. To get crafts class back for pupils, makers, mindset for collaboration, pupil’s different interests, and sharing is in search. Craft is a compulsory learning-by-doing subject for pupils in grades one to seven. The activities are based on craft expression, design and technology (CDT). This research is part of national endeavours to develop innovative CDT as a basic education subject. This paper explores two case studies in which technical work and textile work teachers taught together in a shared learning environment, rather than in traditionally separate learning environments divided into soft and hard materials. The aim is to develop criteria for a new kind of learning environment that would promote innovation learning in pedagogical innovation processes. The first study used a mixed methods approach, including systematic observation, inquiry and pair interviews of five co-teaching teams in primary school, to test the new teaching culture. The second study used an experience sampling method in the form of a mobile application to reveal various parts of pupils' design and making processes in the school setting. The key finding is that collaborative teams can support teachers’ and pupils’ innovation learning activities when the work is supported by shared spaces, practices, and new tools. Preconditions for students’ pedagogical innovation process enhancing makerspaces in the context of formal comprehensive education are discussed in relation to learning outcomes, traditional workshops, learner differences and pedagogical innovation process